Tinjauan Yuridis-Normatif terhadap Penetapan Nomor 14/Pdt.P/2017/Pa.Jmb tentang Isbat Nikah Pasangan Mualaf - Redha, M. Alfar (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2023)
"Isbat nikah" is granted to a husband and wife who have married according to Islamic customs but have not been legally registered with the state, rendering the marriage not legally valid. Due to the absence of a marriage certificate, resolving such marriages through legal means becomes challenging. This differs from the "marriage isbat" application in determination Number 14/Pdt.P/2017/PA.Jmb. In this determination, the Panel of Judges refers to a marriage solemnized according to Buddhism by a husband and wife before their conversion to Islam, or after their conversion to Islam, without renewing the Islamic marriage contract. The research aims to comprehend the legal and normative considerations of the Panel of Judges in approving the marriage isbat request. Normatively, the Panel of Judges confirmed the validity of a marriage performed in a non-Islamic manner (Buddhist) before the couple's conversion to Islam, based on the opinion of Al-Shāfi'i, and applied the principle of jurisprudence prioritizing the prevention of harm over seeking benefit. Additionally, the Panel of Judges refrained from mandating the two Petitioners to remarry, as doing so could potentially lead to legal complexities if the remarriage were to follow Islamic religious procedures.